Examining the legal framework governing the electronic conduct of general assembly meetings in public shareholding companies in Jordan - Althunibat, Abdullah Omar; Al-Rawashdeh, Mohammad Hussein Kassab; Almajali, Osama Nahar Ismail; Awaisheh, Salah Mohammed; Al-Wreikat, Eman Ibrahim; Hmaidan, Ruba Mohammad; Al-Shabatat, Mohammed Ali Zaal; Alhendi, Noor Issa (Research Journal in Advanced Humanities, 2026)
This study analyzes the legal framework for electronic general assembly meetings in Jordanian public shareholding companies amidst digital transformation. It assesses whether current laws uphold process validity, corporate decision integrity, and shareholder rights protection. The research notes that while Jordanian law acknowledges electronic meetings, it lacks detailed procedures, leading to challenges like verifying shareholder identity, quorum calculation, and electronic voting integrity. In contrast, EU regulations, particularly the Shareholder Rights Directive, offer a more robust framework by promoting electronic participation and transparency. The pandemic has further accelerated these developments in the EU. The study concludes that for effective electronic meetings, Jordan needs comprehensive legislation to ensure secure mechanisms for identity verification and voting, enhance regulatory oversight, and align with international digital governance standards.